Associations between immune competence phenotype and stress response in sheep - Schiller, Kaleiah; Monk, Jessica E.; Lee, Caroline; Horback, Kristina (Frontiers in Animal Science, 2023)
Immune competence in domestic sheep is gaining more attention in genetic selection programs that seek to enhance flock immunity and animal welfare. A goal of many programs is to identify behavioral phenotypes that indicate stress-coping strength, as well as disease resilience. The current study set out to explore the relationship between immune responsiveness, physiological stress, and behavioral response among sheep that had been selected for ‘low’ (LR) or ‘high’ (HR) response to cell-mediated and antibody-mediate reactivity to a clostridial vaccine. Multiparous ewes were placed in four experiments which exposed the animals to various threats including, dog presence, human proximity, visual isolation from flock, and physical restraint. To evaluate the consistency of behavioral phenotypes, all ewes were placed in the test circuit one year later. Basal body temperature (via iButton) and serum cortisol concentrations were collected prior to and after the circuit each year. Immune group (HR vs. LR) was not found to be related to behavioral performance during the dog, human, isolation, or restraint challenge. Immune group categorization was also unrelated to pre- and post-cortisol concentrations, and the change in cortisol concentrations during testing. There was a negative relationship identified between response to visual isolation and change in cortisol response during testing, indicating that sheep which were more active or agitated during visual isolation from the flock experienced less of an increase in serum cortisol levels and were perhaps experiencing a negative, high arousal state compared to less reactive sheep (e.g., freeze behavior) (χ2(4, N=99) = 42.72 , P <0.0001). There was also a post hoc, positive relationship identified between weight measurements and immune group, such that individuals with greater body weight were more likely to be in the high immune responsiveness group (P= 0.01). Specifically, for every unit increase in weight, there was a ~49% chance of being categorized in the HR group. This is relevant for selection programs because producers that seek to enhance immune responsiveness and performance may be able to select sheep that carry a greater body mass, and while not found in the present study, could lead to greater flock immunity.